Tailored Silicon/Carbon Compounds for Printed Li–Ion Anodes. Issue 8 (13th May 2020) - Sukkurji, Parvathy Anitha; Issac, Ibrahim; Singaraju, Surya Abhishek; Velasco, Leonardo; Hagmann, Jasmin Aghassi; Bessler, Wolfgang; Hahn, Horst; Botros, Miriam; Breitung, Ben
Abstract: Silicon (Si) has turned out to be a promising active material for next‐generation lithium‐ion battery anodes. Nevertheless, the issues known from Si as electrode material (pulverization effects, volume change etc.) are impeding the development of Si anodes to reach market maturity. In this study, we are investigating a possible application of Si anodes in low‐power printed electronic applications. Tailored Si inks are produced and the impact of carbon coating on the printability and their electrochemical behavior as printed Si anodes is investigated. The printed Si anodes contain active material loadings that are practical for powering printed electronic devices, like electrolyte gated transistors, and are able to show high capacity retentions. A capacity of 1754 mAh/gSi is achieved for a printed Si anode after 100 cycles. Additionally, the direct applicability of the printed Si anodes is shown by successfully powering an ink‐jet printed transistor. Abstract : Powering printed electronics : Nano silicon (Si) is an attractive candidate for lithium‐ion batteries (LIBs) in comparison to graphite, since it delivers 10 times more capacity than commercially available graphite electrodes. The carbon coated Si composites are demonstrated as a potential anode material for LIBs and possess stable capacity for >100 cycles. Our study found out that full cells fabricated with printed Si coated carbon composite anode are able to power the printed transistor circuitry.